Lightning protection methods for wind turbine blades: an alternative approach - Mucsi, Viktor; Ayub, Ahmad Syahrir; Muhammad-Sukki, Firdaus; Zulkipli, Muhammad; Muhtazaruddin, Mohd Nabil; Mohd Saudi, Ahmad Shakir; Ardila-Rey, Jorge Alfredo (MDPI, 2020)
Lightning strikes happens in a fraction of time, where they can transfer huge amounts of charge and high currents in a single strike. The chances for a structure to be struck by lightning increases as the height increases; thus, tall structures are more prone to lightning. Despite the existing lightning protection systems available for wind turbine blades, there are still many cases reported due to the fact of damage caused by lightning strike. Owing to that, the present work introduces a new approach for a lightning protection system for wind turbine blades where preliminary investigations were done using Analysis Systems (ANSYS) Workbench. Two models were developed: one with a conventional type down conductor system and the other with a hybrid conductor system. The recorded findings have been compared and discussed, where it was found that the hybrid conductor system may provide alternative protection from lightning for wind turbine blades.